ANALISIS SWOT DESA WISATA DI KABUPATEN SLEMAN YOGYAKARTA - You She Melly Anne Dharasta; Dhiani Dyahjatmayanti; Kartika Fajar Nieamah (Jurnal Manajemen, 2017)
The development of tourist villages in Sleman district is very fast. Increasing the tourist village in Sleman District, each tourist villages should be able to manage the village well, and can introduce to the community effectively and efficiently. If visitors of the tourist village increase, it will have an impact on the increased revenue so that no difficulty in covering the costs used for the operational tourist village. Therefore it is important to develop a proper, effective, and efficient marketing strategy. The purpose of this study (1) To analyze the threats, opportunities, strengths and weaknesses of each tourist village in Sleman in an effort to increase tourist visits. (2) To know and analyze what tourism marketing strategy that can be applied in Sleman, Yogyakarta. From interviews with village tour managers and via questionnaires circulated to tourists, the average respondent responded positively, although there were still things that were perceived to be lacking, among others, access to transportation roads, parking lots, and road directions. Based on the SWOT analysis the most dominant strategy choice is the SO strategy (Strength Opportunities): the strategy utilizes all the power to create and utilize the greatest opportunities that is (1) Maintenance and development of the environment (2) Increase and multiply the tour package (3) Perform event to attract the tourists. Keywords: SWOT Analysis, Tourist Village, Sleman